İhracatı teşvik tedbirleri ve ihracatta KDV istisnası uygulamaları - Çelik, Mehmet (My University, 2006)
İHRACATI TEŞVİK TEDBİRLERİ VE İHRACATTA KDV İSTİSNASI UYGULAMALARI Gelişmiş ve gelişmekte olan ülkelerin temel amaçları ihracatın artırılması olmuştur. Ülkemizde ihracatı teşvik tedbirleri olarak, öncelikle belirli bir üretim düzeyini yakalayabilmek için ithal ikame politikası izlenmiş daha sonra söz konusu politikanın doğurduğu bir takım sorunlarında etkisiyle 1980 tarihinde alınan ekonomik kararlar çerçevesinde ihracata yönelik sanayileşme stratejisi benimsenmiştir. Bu dönemde ihracatçılar doğrudan parasal teşviklerle desteklenmişlerdir. 1990'lı yıllarda Avrupa Birliği (AB) ve Gümrük Birliği Anlaşması çerçevesinde teşvik siteminin AB ile uyumlaştırılması nedeniyle, doğrudan parasal yardımlar önemli ölçüde kaldırılmış, bölgesel ve vergisel teşvikler ve devlet yardımları adı altında ihracatçılara Ar-Ge, pazarlama, istihdam, eğitim gibi günümüz koşullarına uygun, yararlı teşvikler verilmeye başlanmıştır. AB’ne girme aşamasında olan Türkiye de vergi kanunlarını ve muhasebe sistemlerini uluslararası çalışmalara uyum sağlayacak şekilde düzenlemeye çalışmıştır. Vergilendirmede önemli bir yeri olan Katma Değer Vergisi (KDV) de bu çalışmalar içinde önemli bir paya sahip olmuştur. İhracatı teşvik etmek için Türk Katma Değer Vergisi Kanununda “İhracat İstisnası” başlığı altında düzenlemelere yer verilmiştir. ihracata konu malın üretimi ve tedarikinde katlanılan yüklerin iadesi olan KDV iade sistemi ihracatçıların finansmanında ve uluslararası rekabetlerinde önemli bir unsur olmuştur.

EXPORTATION INCITEMENT MEASURES AND VAT EXCEPTION APPLICATIONS IN EXPORTATION The major goal of both developed and developing countries has been to increase the export. Two major measures on promoting export activities have been implied in Turkey one of which was adopting the policy of imported substitution in the first place to live up to a particular level of production, and then in the year 1980, a strategy on industrialization aimed at exporting activities were adopted in accordance with the economic decisions taken due to some drawbacks caused by the former policy implied. In this period, the exporters were assisted by direct financing. During 1990s, due to the harmonization of the incitement system with the European Union (EU) within the frame of EU and Customs Union Agreement, direct financial aids have been significantly cancelled; useful incitements such as R&D, marketing, employment, education, appropriate to the current conditions are started to be given to exporters under the names of regional and tax related incitements and government aids. Being a country which is en route to strive for the European Union (EU) membership, Turkey tried to rearrange its local tax-related laws and accounting systems so as to harmonize them with international studies. Value Added Tax (VAT), which has an essential role in taxation, has constituted the unbreakable part of such studies. Regulations under the chapter of “Exceptions for Export” were stipulated in Turkish VATL so as to promote exporting activities. VAT refund system, which is the refunding of burdens related to the production and procuration of the property subject to export, has become an important element in the financing of exporters and in their international competition.
Keywords: Maliye; Teşvikler, İhracat_Türkiye; Teşvikler, Vergi_Türkiye